Refinement of Topographical Factor For Estimating Soil Loss and Sediment Yield in Equatorial Regions - Yong, L.K.; Law, P.L; Taib, S.N.L.; Mah, D.Y.S.; Johari, A.H. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This paper aims to improve the Topographical Factor for estimation soil loss and sediment yield in Equatorial region. In the Revised Universal Soil Loss Equation (RUSLE), Topographical factor (LS) is derived as soil loss amount related to gently-inclined plane surface of 72.6ft (22.13m) slope length and 9% slope gradient in United States of America (USA). The terrains in equatorial region (especially at construction sites) comprise of more cone-shaped and pyramid- shaped characterized with steeper slopes and shorter slope lengths as compared to agricultural lands in USA. Topographical Factors (TT, TC & TP) in equatorial region were found as function of sediment yield (SY), surface runoff velocity (RV), and silt and clay compositions (SC). Triangular prism-shaped slope could be used as reference or indicator due to the shape is comparable or almost similar to that of the RUSLE’s gently-inclined plane surface. Cone-shaped and pyramid-shaped showed approximately 80% and 77%, respectively similar to triangular prism-shaped. Therefore, the Topographical Factors for triangular prism-shaped, cone-shaped and pyramid-shaped landscapes in equatorial region: Error! Reference source not found. (Triangular Prism), Error! Reference source not found. (Cone) andError! Reference source not found. (Pyramid).